SME patenting: An empirical analysis in nine countries - Rainer Frietsch; Peter Neuhäusler; Oliver Rothengatter (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
Empirical evidence shows that the distribution of patent applications is highly skewed in terms of company size, with a few large enterprises being responsible for the majority of patent applications. Small and medium-sized enterprises (SMEs), on the other hand, are important players in national innovation systems and are the subject of policy sup-port in many countries. Thus, this study examines the participation rate of SMEs in patenting activities in more detail, differentiating SME patent filings by country and technology area. The analyses are based on a unique, integrated and enriched patent data set of nearly 1.2 million patent applications, built upon PATSTAT data, separating companies into SMEs and large enterprises. The results of descriptive and multivariate analyses reveal that SMEs file fewer interna-tional patents than multinational enterprises (MNEs). However, those SMEs which are active internationally even outperform their larger counterparts in terms of international-ization. It can further be observed that SMEs are more active in emerging technologies, have smaller inventor teams and smaller family sizes on average. Furthermore, patents filed by SMEs are withdrawn more frequently but refused less often. Patents of large firms, on the other hand, have a higher chance of being granted and are cited more frequently.
urn:nbn:de:0011-n-2649037
Keywords: 330